Dynamic regulation of permissive histone modifications and GATA3 binding underpin acquisition of granzyme A expression by virus‐specific CD8+ T cells. Issue 2 (24th November 2015) - Nguyen, Michelle L. T.; Hatton, Lauren; Li, Jasmine; Olshansky, Moshe; Kelso, Anne; Russ, Brendan E.; Turner, Stephen J.
Abstract : Numerous studies have focused on the molecular regulation of perforin (PFP) and granzyme B (GZMB) expression by activated cytotoxic T lymphocytes (CTLs), but little is known about the molecular factors that underpin granzyme A (GZMA) expression. In vitro activation of naïve CD8 + T cells, in the presence of IL‐4, enhanced STAT6‐dependent GZMA expression and was associated with GATA3 binding and enrichment of transcriptionally permissive histone posttranslational modifications (PTMs) across the Gzma gene locus. While GZMA expression by effector influenza A virus specific CTLs was also associated with a similar permissive epigenetic signature, memory CTL lacked enrichment of permissive histone PTMs at the Gzma locus, although this was restored within recalled secondary effector CTLs. Importantly, GZMA expression by virus‐specific CTLs was associated with GATA3 binding at the Gzma locus, and independent of STAT6‐mediated signaling. This suggests regulation of GZMA expression is underpinned by differentiation‐dependent regulation of chromatin composition at the Gzma locus and that, given GATA3 is key for CTL differentiation in response to infection, GATA3 expression is regulated by a distinct, IL‐4 independent, signaling pathway. Overall, this study provides insights into the molecular mechanisms that control transcription of Gzma during virus‐induced CD8 + T‐cell differentiation.